(untitled) (Research, Society and Development, 2023)
There has been a surge in research on Psilocybin-Assisted Therapy (PAT) over the past three decades. PAT has yielded positive results across clinical trials and demonstrated efficacy in treating various mental disorders. However, limited qualitative research exists that explores peoples’ experiences of PAT. This study aims to review the current literature on the experiences of individuals that have participated in PAT, as well as individuals that have facilitated PAT. This study aims to increase our understanding of PAT to guide and improve therapeutic effectiveness. A scoping review was conducted from English language studies published in peer-reviewed journals. Searches were conducted from PsycInfo, CINAHL, PubMed, Web of Science, and Cochrane Library databases. Inclusion criteria were qualitative studies involving PAT that were conducted between January 1990 and December 2022; articles published in peer-reviewed journals; and psychedelic practitioners’ experiences of facilitating PAT. In total, 13 articles were extracted to be included in the review. Articles were published between 2017 and 2021, and were divided into (1) Participant Studies (10) and (2) Facilitator Studies (3). Six themes were identified: the influence of set and setting; PAT was personalised and meaningful; PAT can be highly emotive; transcendental experiences; reduction of symptoms and long-lasting changes; and boundaries and responsibility. The literature revealed numerous interrelated therapeutic elements that may have contributed to a meaningful experience during PAT. This may play a role in attaining long-lasting positive therapeutic outcomes. The studies were varied and highlighted the usefulness of further exploring PAT.